Stigma and discrimination, coping strategy and caregiving of wife infected with HIV/AIDS - Md. Zain, Rajwani (American-Eurasian Network for Scientific Information (AENSI Publisher), 2013)
The number of women with HIV infection and AIDS has increased steadily worldwide The majority of new HIV cases in women are the result of sexual behaviors.A research on issues and concern of wives who have been infected with HIV and lost their husbands to AIDS was conducted in 2008 in the northern part of Malaysia.The main objective of the study was to explore what are some of the impacts of HIV/AIDS on women in Malaysia. A qualitative research was used as a method of the study.An in-depth interview has been conducted with seven women who were infected with HIV from their husbands in northern part of Malaysia. Through the study three main themes were identified, namely; stigma and discrimination, coping strategies, and care giving.Results showed that many of these women are suffering from stigma and discrimination, isolated, and insulted by family and society.Many became withdrawn and feeling helpless with their HIV status. Fear of others knowing about their HIV continues and there was nobody to turn to for psycho social help. Caregiving has also been a problem after their husbands died of AIDS. This study suggested that some plan of action should be taken in order to help these women to cope with their HIV status. Government and non-government agencies should continue their activities to reduce stigma and discrimination, increase health and social services especially in the northern region of Malaysia.